STRATEGIES FOR TRANSLATING REALIA - Muminov Elyor Turayevich (World Scientific Research Journal, 2025)
Translation is more than linguistic transfer; it is an act of cultural negotiation. While most words have equivalents across languages, certain terms are deeply culture-bound and resist direct translation. These terms, called realia, denote real-world objects, customs, institutions, and phenomena tied to the daily life, geography, and traditions of a particular community (Vlahov & Florin, 1980/2012). Examples include kimono (Japanese clothing), bazaar (Middle Eastern market), fjord (Norwegian geography), or Thanksgiving (American holiday). For translators, realia present a dilemma: how much of the source culture should be preserved? If the translator retains the original form, readers may feel disoriented. If the translator replaces the item with a local equivalent, cultural nuance is lost. This problem has long preoccupied scholars. Toury (1995) described it as a tension between adequacy (faithfulness to the source text) and acceptability (adaptation to target culture norms). Venuti (1995) later reframed this as foreignization versus domestication, linking translators’ choices to broader ethical issues of cultural representation.